THE IMPACT OF WORK DISCIPLINE ON CIVIL SERVANT PERFORMANCE AT THE DEPARTMENT OF MANPOWER AND TRANSMIGRATION (RIAU PROVINCE) - Kevin Delfha Afhandi; Rodi Wahyudi (Indonesian Journal of Social Sciences, Policy and Politics, 2025)
Work Discipline is one of the factors that causes employee performance to decline. Employees who implement good work discipline will produce good performance as well. The purpose of this study was to determine the effect of work discipline on the performance of state civil servants at the Riau Province Manpower and Transmigration Service. This study uses quantitative methods and data collection methods using Observation, questionnaires, and Documentation methods, then analyzed using descriptive statistical techniques and simple linear regression using the SPSS 30 application. The sampling technique uses the Simple Random Sampling method, namely 34 employees were used as research samples. From the results of the study, it can be concluded that the work discipline variable has a significant positive effect on the performance variable of 99.6% while 0.4% is influenced by other factors not examined in this study.